Anti-glioma trichobamide A with an unprecedented tetrahydro-5H-furo[2, 3-b]pyrrol-5-one functionality from ascidian-derived fungus Trichobotrys effuse 4729. Issue 10 (15th January 2019) - Chen, Senhua; Shen, Hongjie; Zhang, Panpan; Cheng, Hongwei; Dai, Xingliang; Liu, Lan
Abstract : Trichobamide A (1 ), a novel pyrrocidine alkaloid with an unprecedented tetrahydro-5 H -furo[2, 3- b ]pyrrol-5-one moiety, was isolated from the ascidian-derived fungus Trichobotrys effuse 4729. Abstract : Trichobamide A (1 ), a novel pyrrocidine alkaloid with an unprecedented tetrahydro-5 H -furo[2, 3- b ]pyrrol-5-one moiety, was isolated from the ascidian-derived fungus Trichobotrys effuse 4729. Trichobamide A (1 ) showed significant inhibition of the proliferation of two glioma cell lines, U251 and SNB19. It induced the up-regulation of P53 expression, which in turn induces the up-regulation of downstream pro-apoptotic gene expression and the down-regulation of anti-apoptotic gene expression.